(untitled) (Architecture Image Studies, 2025)
The current study aimed to reveal the nature of the relationship between mental alertness and both visual attention and image-based visual perception among deaf and hard-of-hearing students enrolled in educational integration programs in Najran region of Saudi Arabia. It also sought to test the ability of mental alertness to predict levels of visual attention and visual perception in this group, within a cognitive psychological perspective that focuses on attentional regulation. The study relied on a descriptive correlational approach, and the study sample consisted of 114 deaf and hard-of-hearing students. The Children and Adolescents Mindfulness Scale (CAMM) was applied, along with the Visual Attention Scale and the Picture-Based Visual Perception Scale. Statistical analyses were performed using arithmetic means and standard deviations, Pearson’s correlation coefficient, and simple linear regression analysis. The results showed that levels of mental alertness, visual attention, and picture-based visual perception were moderate to high. They also revealed statistically significant positive correlations between mental alertness and both visual attention and picture-based visual perception. The regression analysis results indicated that mental alertness contributes significantly to predicting both visual attention and visual perception, explaining a considerable proportion of the variance in these two variables. The study concludes that mental alertness is a regulatory psychological mechanism related to how deaf and hard-of-hearing students direct their attention and process visual information, and emphasizes the importance of viewing visual perception as a cognitive process influenced by the state of consciousness and attentional regulation, rather than merely a direct sensory response.